PENGEMBANGAN E-LKPD BERBASIS PROJECT BASED LEARNING PADA MATERI VIRUS KELAS X SMA - Sandra, Aura; Fitra Suzanti; Irda Sayuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The use of student worksheets in schools is still predominantly print-based and has not fully attracted students’ interest, particularly in virus material, which requires visual, interactive, and contextual presentation. The development of electronic student worksheets based on Project Based Learning is needed as an alternative teaching material that can encourage students’ active participation, creativity, and independence in understanding virus material. This study aimed to determine the validity and quality of electronic student worksheets based on Project Based Learning for virus material in Grade X senior high school. This research employed a Research and Development method using the ADDIE model, which was limited to the Analyze, Design, and Development stages. The research subjects consisted of four validators, namely two Biology Education lecturers and two Biology teachers, as well as limited trial respondents involving 10 Biology Education students and 35 Grade X students of SMA Negeri 5 Pekanbaru. The instruments used were validation sheets and respondent questionnaires, and the data were analyzed using mean scores. The results showed that the developed electronic student worksheets obtained a validation score of 3.68, which was categorized as highly valid. The results of the first limited trial obtained a score of 3.70, while the second limited trial obtained a score of 3.76, both categorized as very good. Overall, the quality of the electronic student worksheets obtained a score of 3.71, which was categorized as very good. Therefore, the electronic student worksheets based on Project Based Learning for virus material are feasible to be used as Biology teaching materials for Grade X senior high school students.